Tropicalization of curve arrangement complements and arroids - Aksnes, Edvard (MATHEMATICA SCANDINAVICA, 2025)
We define arroids as an abstract axiom set encoding the intersection properties of arrangements of curves. The tropicalization of the complement of an arrangement of curves meeting pairwise transversely is shown to be determined by the associated arroid. We give conditions for when the cohomology of the complement of an arrangement is computable using tropical cohomology, and we give criteria for when the complement is a maximal variety in terms of tropical geometry.